If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 42 = 10x + 56 Reorder the terms: 42 + 12x = 10x + 56 Reorder the terms: 42 + 12x = 56 + 10x Solving 42 + 12x = 56 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 42 + 12x + -10x = 56 + 10x + -10x Combine like terms: 12x + -10x = 2x 42 + 2x = 56 + 10x + -10x Combine like terms: 10x + -10x = 0 42 + 2x = 56 + 0 42 + 2x = 56 Add '-42' to each side of the equation. 42 + -42 + 2x = 56 + -42 Combine like terms: 42 + -42 = 0 0 + 2x = 56 + -42 2x = 56 + -42 Combine like terms: 56 + -42 = 14 2x = 14 Divide each side by '2'. x = 7 Simplifying x = 7
| 0.4+8=12 | | -9=2(w+3)-5w | | 3-(2x+2)=x-(3x-5) | | 4+7(x-8)=9-3(x-4) | | 1-4y=1 | | -14=-4+5x+3x | | 33m-14+14=33 | | x-7=34-7(x+7) | | 4x-1=113 | | 124-v=185 | | -7+3y=-16 | | 16+8y=80 | | 4v-4=-24 | | 2(x-4)-3=7-4x | | 3=(-6)+x | | -5p=0 | | -x-10y=-24 | | 56=2(15)+2w | | -2y+30=5y-5 | | 3x+5x+-4=-14 | | 5+2*[3(x+5)-(3x+11)]=11-4x | | 3x+3x+4x+2x= | | 2-4d=0 | | 3y-5t+10=36 | | -5/9y25 | | y=1E+06X+17211 | | 10u-3u=42 | | (X-2)2+(y+5)2=12 | | 69x+13=151 | | -30=5+5y | | 5x*y=2720 | | p/3=2p/3=1/4 |